Mechanisms governing the pioneering and redistribution capabilities of the non-classical pioneer PU.1 - Julia Minderjahn (Nature Portfolio, 2020)
PU.1 is a master TF of hematopoietic lineage differentiation. Here the authors analyse properties of PU.1 DNA-binding in vitro and genome-wide in vivo across different cell types with native or ectopic PU.1 expression, and uncover the mechanisms governing the pioneering and redistribution capabilities of the non-classical pioneer PU.1.